Design And Implementation Of Computer -Patient Record (CPR) For Endemic Diseases, (MoH) - Sudan - Ahmed Farag, Omnia Farouk (2004)
This paper suggests new technologies could be derived to provide powerful, high quality computer patient record solutions that combine productive software, powerful healthcare guidance, and integrated solutions to help leading healtcare providers improve their document workflows and records management systems to deliver higher quality patient care.